The era of digital activism. (1st January 2013) - Shah, Vivek; Sivitanides, Marcos; Mehta, Mayur
Since the advent of the internet, the world has undergone a digital revolution. The new tools of social media have reinvented social activism, heralding the era of digital activism. This paper provides a framework and terminology for understanding digital activism. It describes the fundamental differences between traditional activism, as it existed before internet-driven social media, and as it manifests itself now using the tools of digital technology. The paper analyses the potential risks and benefits of digital activism, both of which are amplified with the use of internet-based social media. The paper sets a framework that explains how the use of activism can have a positive impact and bring about the activists' desired effect. On the other hand, activism can have a negative result in terms of friction in the public domain. The digital aspect of activism amplifies the entire process. Activism has become a higher risk/higher benefit activity.